Assessment of the prevalence of physical and mental fatigue in myasthenia gravis and its correlation with other motor and nonmotor symptoms - (:unkn) unknown (My University, 2021)
Objective: Muscle weakness and easy fatigability is the clinical hallmark of myasthenia gravis (MG). However, the opinion has emerged that physical and mental “fatigue” can be seen in MG. Background: The effect of fatigue on quality of life, irrespective of motor deficit, has not been elucidated . The aim of this study is to evaluate the frequency of fatigue symptoms in myasthenic patients with nearly full muscle strength and the effect of fatigue on the quality of life by assessing its correlation with other nonmotor symptoms, such as depression. Design/Methods: Fifty three patients with ocular MG or mild generalized MG with remission or minimal manifestations, and 53 healthy volunteers were recruited for the study. The patient group completed questionnaires measuring the severity of MG and quality of life [Myasthenia Gravis Foundation of America (MGFA), MGFA Post-İntervention Status (MGFA-PIS), MG Composite Scale (MGC), and MG-Activities of Daily Living Profile (MG-ADL)], while both the patient and control groups completed scales assessing fatigue [Fatigue Assessment Scale (FAS) and Fatigue Impact Scale (FIS)], depression [Beck Depression Inventory (BDI)], and sleep [Epworth Sleepiness Scale (ESS)]. Results: FAS, FIS physical and BDI scores were significantly higher in the patients compared to the control group (p=0.003, p=0.001, and p=0.003, respectively). In the patient group, depressive symptoms and daytime sleepiness were significantly higher in females than in males (p=0.019 and p=0.013). The mean values of FIS total and cognitive scores were significantly higher in patients with generalized MG than in patients with ocular MG (p=0.033 and p=0.045). Correlation analysis showed that fatigue scores correlated with motor signs, and had a negative impact on quality of life. Fatigue was also associated with depression and daytime sleepiness. Conclusions: Fatigue and fatigability can be seen independently from muscle weakness in MG. Increasing the recognition of fatigue and taking precautions will positively affect the quality of patients’ life.